2020
DOI: 10.1021/acsnano.0c07721
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Immune Cold and Reprogramming Immunosuppressive Tumor Microenvironment with Red Blood Cell Membrane-Camouflaged Nanobullets

Abstract: Nanomedicine, acting as the magic bullet, is capable of combining immunotherapy with other treatments to reverse a cold tumor (immune depletion) into a hot tumor. However, how to comprehensively inhibit the immunosuppressive tumor microenvironment (TME) remains a major challenge for immunotherapy to achieve the maximum benefits. Thus, a strategy that can simultaneously increase the recruitment of tumor infiltrating lymphocytes (TILs) and comprehensively reprogram the immunosuppressive TME is still urgently nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 219 publications
(147 citation statements)
references
References 56 publications
0
147
0
Order By: Relevance
“…In addition, the enhanced synergistic effect of PTX and CUR that was mediated by HA-PAAVB NPs could inhibit primary breast cancer growth and their lung metastasis. Therefore, the intelligent drug delivery system [ [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] based PAAVB copolymer presented in this paper could provide an effective platform that combines chemo- and immune-therapeutics for fighting against various malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the enhanced synergistic effect of PTX and CUR that was mediated by HA-PAAVB NPs could inhibit primary breast cancer growth and their lung metastasis. Therefore, the intelligent drug delivery system [ [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] based PAAVB copolymer presented in this paper could provide an effective platform that combines chemo- and immune-therapeutics for fighting against various malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RBC-LIP-AmB exhibited a distinct ability to neutralize hemotoxin released by the pathogenic fungi, and protected the mice from Candida albicans infection as well as prolonged survival time. Other than the above, RBC membrane can camouflage bovine serum albumin for malignant melanoma metastasis 54 , perfluorocarbon for hypoxia alleviation 55 , ZGGO@mSiO2 for bioimaging and therapy of breast cancer 56 , PAAV-SNO copolymer for immune cold, and reprogramming immunosuppressive tumor therapy 57 .…”
Section: Cell Membrane Vectorsmentioning
confidence: 99%
“…Results showed that both the primary tumor and distant tumor was suppressed significantly after the combinational therapy. Similarly, Yang and co-workers explored the anti-tumor effect of IR1061 mediated NIR II PTT combined with IDO inhibitor (1-MT) 97 . IR1061 and 1-MT were co-encapsulated into nanoparticles self-assembled by a poly (acrylamide-co-acrylonitrile-co-vinylimidazole)-S-nitrosothiols copolymer, PAAV-SNO).…”
Section: Other Strategies To Synergize Nano-based Ptt With Immunotherapymentioning
confidence: 99%